Online text mining for conversational speech recognition - Thong, Kian Hoong. (2013)
Conversational text is a highly varied, and many abbreviations and short forms exist in different languages. To manually enter every single possible term would be difficult, and chances are that certain terms would be missed out. This makes the compilation of conversational texts a difficult task. This project aims to utilize cutting-edge search engines of today, like Google and Bing, to crawl the web for conversational texts to add to the Language Model. It also utilizes certain methods to minimize the clutter that’s present in the final text that will be input into the Language Model.